Spontaneous Rupture of the Internal Iliac Artery in an Elderly Patient: A Case Report Exploring the Possible Role of Klebsiella Pneumoniae Infection - David Pakeliani; Giuseppe Indelicato; Liborio Ferrante; Maurizio Finocchiaro (International Journal of Translational Medicine)
Background: The spontaneous rupture of the internal iliac artery (IIA) is an exceedingly rare vascular event, typically associated with congenital anomalies or degenerative conditions. This report details an unprecedented case of isolated IIA rupture in an elderly patient with evidence of plaque rupture but devoid of congenital vascular pathology. Case Presentation: An 81-year-old Caucasian male presented to the Emergency Department following a syncopal episode and acute right iliac fossa pain. His significant medical history was atrial fibrillation managed with anticoagulation (Apixaban), non-insulin-dependent diabetes mellitus, and recent hospitalization for multidrug-resistant Klebsiella pneumoniae pneumonia. Initial imaging with contrast-enhanced computed tomography revealed an aneurysmatic dilatation of the right IIA, indicative of rupture. An endovascular repair was performed, employing a combination of stent grafts to achieve proximal and distal sealing and to restore vascular continuity. Outcome: The patient exhibited hemodynamic stability throughout the perioperative period and was transferred to the general ward postoperatively. However, he suffered a recurrent rupture on the 30th postoperative day, prompting a second endovascular intervention to extend the graft landing zone into the common iliac artery. Intraoperative findings confirmed localized plaque rupture as the underlying trigger for the initial vessel rupture. He ultimately achieved clinical stability and was discharged on the 35th postoperative day. Discussion: This case illustrates the critical importance of recognizing spontaneous IIA rupture as a potential complication in elderly patients, particularly in the context of recent severe infections. While the relationship between the rupture and the Klebsiella pneumoniae infection remains speculative, this report underscores the necessity of further research into the role of infectious processes in vascular integrity and susceptibility to rupture. Conclusions: The successful management of this rare and complex vascular emergency using endovascular techniques underscores the evolving landscape of minimally invasive interventions. This case contributes to the limited existing literature on spontaneous IIA rupture and highlights the need for increased clinical vigilance regarding atypical presentations in similar patient populations.